Synthesis, characterisation and catalytic testing of pillared clays and lanthanum exchanged ZSM-5 for hydrocarbon conversion - Hartford, Radleigh (Department of Chemical Engineering, 2017)
Pillared clays present interesting possibilities for use as acid catalysts. The present research investigated the effect that pillaring has on the physical and catalytic properties of some smectite clays. The effect of using a hydroxy-Al solution to pillar a predominantly octahedrally ,substituted clay (montmorillonite) and a tetrahedrally substituted clay (beidellite) were compared. The effects of pillaring tetrahedrally substituted clays with different swellable properties (beidellite, SMM, and Ni-SMM) were investigated. In an attempt to enhance the acidic properties of the pillars, montmorillonite was pillared with a hydroxy-Al solution containing tetraethyl orthosilicate. Montmorillonite was also pillared with a hydroxy-Ni/Al solution in an effort to produce a clay with an increased pillar density. The pillared and unpillared clays were characterised using x-ray diffraction, surface area measurements, thermogravimetric analysis and ammonia TPD. The possible shape selective properties of the different clays for the conversion of trimethylbenzene were investigated, and the catalytic activities and product selectivities of these clays for high pressure propene oligomerisation were studied.